Application of Biocatalysis to on‐DNA Carbohydrate Library Synthesis. (28th February 2017) - Thomas, Baptiste; Lu, Xiaojie; Birmingham, William R.; Huang, Kun; Both, Peter; Reyes Martinez, Juana Elizabeth; Young, Robert J.; Davie, Christopher P.; Flitsch, Sabine L.
Abstract: DNA‐encoded libraries are increasingly used for the discovery of bioactive lead compounds in high‐throughput screening programs against specific biological targets. Although a number of libraries are now available, they cover limited chemical space due to bias in ease of synthesis and the lack of chemical reactions that are compatible with DNA tagging. For example, compound libraries rarely contain complex biomolecules such as carbohydrates with high levels of functionality, stereochemistry, and hydrophilicity. By using biocatalysis in combination with chemical methods, we aimed to significantly expand chemical space and generate generic libraries with potentially better biocompatibility. For DNA‐encoded libraries, biocatalysis is particularly advantageous, as it is highly selective and can be performed in aqueous environments, which is an essential feature for this split‐and‐mix library technology. In this work, we demonstrated the application of biocatalysis for the on‐DNA synthesis of carbohydrate‐based libraries by using enzymatic oxidation and glycosylation in combination with traditional organic chemistry. Abstract : Cracking the codes : Biocatalysis is particularly beneficial for DNA‐encoded libraries, as it is highly selective and can be performed in aqueous environments. In this work, we demonstrated the application of biocatalysis for the on‐DNA synthesis of carbohydrate‐based libraries by using enzymatic oxidation and glycosylation in combination with traditional organic chemistry.